Genomics, obesity and the struggle over responsibilities - Korthals, Michiel; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This volume addresses the overlapping aspects of the fields of genomics, obesity and (food) ethics. It is unique in its examination of the implications of genomics for obesity from an ethical perspective. Genomics covers the sciences and technologies involved in the pathways that DNA takes until the organism is completely built and sustained: the range of genes (DNA), transcriptor factors, enhancers, promoters, RNA (copy of DNA), proteins, metabolism of cell, cellular interactions, organisms. Genomics offers a holistic approach, which, when applied to obesity, can have surprising and disturbing implications for the existing networks tackling this phenomenon and for fundamental ethical notions, strategies and practices. In the book several strategies to match genomics, obesity, society and ethics are studied, and a happy match is proposed based on a pragmatist ethical framework. The ethical framework presented is inspired by the interaction between a procedural perspective emphasizing the necessity of consultative and participatory organizational relationships in the new interfaces between (nutri)genomics, medicine and food, and a substantive perspective that both cherishes individual autonomy and embeds it in socio-cultural contexts.
Content.- Contributors.- Acknowledgements.- Editor?s Preface.- Part I Introduction.- 1 Challenges of Genomics to Obesity and Traditional Ethics; Michiel Korthals.- 2 Genomics and Obesity from a Pragmatist Point of View; Michiel Korthals.- Part II Concepts of Obesity and Genomics; what can Genomics imply for Society?.- 3 Behaviour, Environment or Body: Three Discourses on Obesity; Tsjalling Swierstra.- 4 Contesting the Obesity Epidemic: Elements of a Counter Discourse; Henk van den Belt.- 5 Three Main Areas of Concern, Four Trends in Genomics and Existing Deficiencies in Academic Ethics; Michiel Korthals.- 6 Obesity Genomics: Struggle over of Responsibilities; Michiel Korthals.- Part III Futures, Genetic Testing and Enhancement.- 7 Obesity in 2020. Three Scenarios on Techno-socio-ethical Co-evolution; Tsjalling Swierstra and Jozef Keulartz.- 8 Direct-to-Consumer Genetic Testing. How the Promise of a Personalised Approach is being Squandered; Henk van den Belt.- 9 Genomics, Obesity and Enhancement; Maartje Schermer.- Part IV Cultural Framing of Genomics-Obesity in The Netherlands and Italy.- 10 Obesity and Genomics in the Netherlands; Michiel Korthals.- 11 Obesity and Genomics in Italy; Mara Miele.- 12 Holland-Italy: a Match too far?; Michiel Korthals.- Part V Food and Health: Toward a Happy Match of Genomics, Obesity and Values.- 13 Prevention of Obesity and Personalized Nutrition: Public and Private Health; Michiel Korthals.- 14 Expectations and Disappointments of the Human Genome. The Genomics Health Card and Anti Obesity Pills; Michiel Korthals.- 15 Matching Nutrigenomics, Society and Values; Michiel Korthals.- Part VI Conclusion.- 16 Conclusion: Beyond Genomics and Obesity; Michiel Korthals.- Biographies of Contributors to the Book.- Index.
Electronic reproduction.
Keywords: Obesity -- Genetic aspects; Obesity -- Moral and ethical aspects; Food -- Moral and ethical aspects; Electronic books